Kinship networks and resiliency to flooding of Pagatban riverside communities in Negros Oriental - Oracion, Enrique G. (2015)
This article investigates the case of riverside communities at Pagatban River in Negros Oriental, Philippines which not only found the river as a source of material resources and services but also as their main cause of devastation. Using primarily survey research, complemented by secondary data analysis and key informant interviews, this article argues that the perennial flash flooding and overflowing of Pagatban River during heavy rains and typhoons had established among the affected households a culture of disaster. However, the disastrous impacts of flooding were not uniformly felt by households located in the different sections of the river which allowed assistance to flow through kinship networks from the less to the more vulnerable households. Being located at the chokepoint of the river where overflowing of water usually happened, midstream households were most vulnerable with the highest amount of damages on their farms and other properties. The number of households from this section is highest among those that received assistance from relatives within the community as compared to upstream and downstream households. It is recommended that community-based disaster preparedness program must also strengthen kinship network to address the needs of more vulnerable households when external assistance is limited or absent.
Keywords: Kinship -- Negros Oriental; Natural disasters